Ontology-based decision support system in entomophages production - Chernova, I. (Energy and Automation, 2026)
The article explores the issue of developing a decision support system based on ontologys in the production of entomophages for the biologization of plant protection, which is due to the need to increase the efficiency of the management processes of this production. The use of ontologies makes it possible to generalize and systematize knowledge about the processes of entomophages production based on the results of previous research, technological experience of specialists, analysis of scientific papers, and modern software tools. The aim of the study is to develop a decision support system based on ontologies in the production of entomophages. Research methods – systemic and synergistic approaches, ontological engineering, machine learning, publicly available software environments Visual Understanding Environment and FreeMind, and the Scilab computer mathematics system. An analysis of recent research and publications on the creation of decision support systems based on ontologies was conducted. A decision support system based on ontologys in the production of entomophages has been developed, the structure of which is presented in the form of an associative map using the FreeMind software environment. The components of the system are the Visual Understanding Environment software environment; user interface; ontological knowledge base, which contains classes, concepts and built-in ontologies. System functions: decision-making support regarding the quality of entomological products and the level of technological controllability of production processes under conditions of uncertainty; automated analysis, structuring and digitalization of knowledge. The research results allow to increase the level of automation of processes for managing the production of entomophages and the competence of the decision-maker, and can be used in the creation of artificial intelligence systems in the production of biological plant protection products Recieved 2025-12-25 Recieved 2026-01-12 Accepted 2026-02-11